Resource potentials of composting the organic wastes stream from municipal solid wastes compositions arising in Nigerian cities - Kasim, Rozilah; Harir, Adamu Isa; Ishiyaku, Bala (Scientific Research Publisher, 2015)
The paper presented an assessment of the resource potentials of composting organic waste mate-rials arising from the municipal solid waste stream from cities in Nigeria. Through a review of quantitative data, the composition of municipal solid waste arising within cities in Nigeria was examined in order to identify the potentials for composting organic materials from the waste stream composition. The data showed that the average majority of the waste stream was organic materials which implied high potentials for composting organic waste materials from Nigerian ci-ties. The review also identified further potentials for composting was associated with the large population and the majority of them engaged in agriculture, as a high potential market for com-post manure in Nigeria. There were more potentials derivable from the current policies of im-porting and supplying chemical fertilizer with huge subsidies for domestic agriculture in the country. The need to substitute these policies of chemical fertilizer with the use of compost ma-nure implied high potentials for composting in the country. The paper also identified numerous benefits of composting in general and with particular reference to the Nigerian situation which in-cludes, among others a reduction of the vast quantity of solid waste for final disposal, reducing air pollution and ground water leachate and also employment generation and increased income. Therefore, the paper recommended a deliberate government policy to promote composting of or-ganic solid wastes material and marketing of compost manure to substitute the current policies of importing chemical fertilizer with subsidy for domestic agriculture as a strategy to achieve sus-tainable waste management in Nigeria.